18.2k views
0 votes
4(x-6)+6=6x-9 what is x

User Dmpop
by
5.0k points

2 Answers

2 votes

Ah cute.

We have the following equality


4(x-6)+6=6x-9.

First we will distribute the parentheses on the left side to get


4x-24+6=6x-9.

Then move x-terms to left side and other terms to right side


-2x=9.

Finally divide both sides of equation by -2 to get


x=\boxed{-(9)/(2)}.

Hope this helps.

User Annalena
by
5.8k points
3 votes

Answer:

− 9/2

Explanation:

Let's solve your equation step-by-step.

4(x−6)+6=6x−9

Step 1: Simplify both sides of the equation.

4(x−6)+6=6x−9

(4)(x)+(4)(−6)+6=6x+−9(Distribute)

4x+−24+6=6x+−9

(4x)+(−24+6)=6x−9(Combine Like Terms)

4x+−18=6x−9

4x−18=6x−9

Step 2: Subtract 6x from both sides.

4x−18−6x=6x−9−6x

−2x−18=−9

Step 3: Add 18 to both sides.

−2x−18+18=−9+18

−2x=9

Step 4: Divide both sides by -2.

−2x/−2=9/−2

x=−9/2

User Iamdave
by
5.4k points